Central Nervous System Histoplasma-Associated Post-infectious Inflammatory Response Syndrome (Histo-PIIRS) - Dean, Owen (J Clin Immunol, 2021)
We present a case of central nervous system (CNS) histoplasmosis in a previously healthy adult with hepatitis C (HCV) presenting with neurological symptoms refractory to antifungal therapy and ventriculoperitoneal (VP) shunting 4 months after initial diagnosis. Persistent symptoms were thought to be inflammatory rather than infectious given negative cerebrospinal fluid (CSF) and serum fungal antigens. The patient promptly improved after initiation of corticosteroid therapy. Elevated CSF cytokines and regional enhancement on brain MRI resolved with corticosteroid treatment. This is the first case of Histoplasma-associated post-infectious inflammatory response syndrome (Histo-PIIRS) documented by CSF cytokine reduction in response to corticosteroid therapy.